All-optical switching and two-photon absorption effects in long- period gratings in As2Se3 chalcogenide fibre - Nguyen, H; Grujic, T; Finsterbusch, K; Mägi, E; Fu, L; Kuhlmey, B; De Sterke, C; Eggleton, B (2007)
We show that two-photon absorption can actually improve the performance of a long-period grating switch in highly nonlinear As2Se3 chalcogenide fibre. We demonstrate numerically and experimentally low power switching behavior at pulse intensities around 65MW/cm2.